2001
DOI: 10.1093/jn/131.12.3216
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Long-Chain Polyunsaturated Fatty Acids from Different Sources Affect Fat and Fatty Acid Excretions in Rats

Abstract: Several sources of long-chain polyunsaturated fatty acids (LCP) have been evaluated for infant-formula supplementation. These sources differ in their chemical structure [triglyceride (TG) or phospholipid (PL)], arrangement of fatty acids on the TG or PL backbone, fatty acid composition and presence of other lipid components. All of these characteristics influence fat digestion, may affect fat and fatty acid absorption, and hence, LCP bioavailability and metabolism in infancy. The main objective of this work wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Overall total lipid digestibility was lowest ( P < 0.02) in KO-fed rats which may be accounted for by fatty acids in KO being associated with PL. Amate and Ramirez [30] observed reduced absorption of n-3 LC-PUFAs in rats fed PL-rich pig brain. In contrast, infants and pre-term infants fed LC-PUFA PL as egg lecithin improved fat absorption [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Overall total lipid digestibility was lowest ( P < 0.02) in KO-fed rats which may be accounted for by fatty acids in KO being associated with PL. Amate and Ramirez [30] observed reduced absorption of n-3 LC-PUFAs in rats fed PL-rich pig brain. In contrast, infants and pre-term infants fed LC-PUFA PL as egg lecithin improved fat absorption [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…FA absorption in the small intestine has been found equivalent for both the PL- and TG-derived compounds [3438]. It has, however, been proposed that the different PL and TG ester forms could determine in which blood pool (free FAs, outer versus inner layer of chylomicrons, different lipoprotein particles) the FAs end up [39].…”
Section: Different Tissue Distribution Of Fas From Pl and Tg Estermentioning
confidence: 99%
“…It has been shown that dietary AA-PL is at least as efficacious as dietary AA-TAG to supply the developing organs with AA [155]. No direct information relates to the effects of DHA-TAG versus DHA-PL in this context [2, 5, 6, 38, 58, 106, 155]. …”
Section: Lipids In Human Milk and Infant Formulamentioning
confidence: 99%